2021
DOI: 10.3390/microorganisms10010089
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Whole-Genome Analysis of Russian Foodborne Multidrug-Resistant Salmonella Infantis Isolates

Abstract: Non-typhoidal Salmonella infections remain a significant public health problem worldwide. In this study, we present the first detailed genomic analysis report based on short-read (Illumina) whole-genome sequencing (WGS) of 45 multidrug-resistant (MDR) Salmonella enterica subsp. enterica serotype Infantis isolates from poultry and meat product samples obtained in Russia during 2018–2020, and long-read (MinION) WGS of five more representative isolates. We sought to determine whether foodborne S. Infantis have ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 60 publications
(107 reference statements)
3
6
0
1
Order By: Relevance
“…Indiana, which was considered the most resistant serovar in this study, carries plasmid types IncX1_1, IncHI2_1, IncHI2A_1, and Col156_1; these plasmids have been associated with the acquisition of resistance to different classes of antimicrobials, including aminoglycosides, sulfonamides, tetracyclines, quinolones, polymyxins, and β-lactams ( 52 , 53 ). Furthermore, our findings demonstrated that the plasmid type IncX1, in addition to IncFII(S) and IncFIB(S), is the key carrier of antimicrobial resistance determinants in Salmonella , which is in agreement with previous findings from China and elsewhere ( 54 57 ). Hence, the presence of these plasmids in the studied isolates is of major concern and may mediate the horizontal transmission of antimicrobial resistance along the food chain.…”
Section: Discussionsupporting
confidence: 93%
“…Indiana, which was considered the most resistant serovar in this study, carries plasmid types IncX1_1, IncHI2_1, IncHI2A_1, and Col156_1; these plasmids have been associated with the acquisition of resistance to different classes of antimicrobials, including aminoglycosides, sulfonamides, tetracyclines, quinolones, polymyxins, and β-lactams ( 52 , 53 ). Furthermore, our findings demonstrated that the plasmid type IncX1, in addition to IncFII(S) and IncFIB(S), is the key carrier of antimicrobial resistance determinants in Salmonella , which is in agreement with previous findings from China and elsewhere ( 54 57 ). Hence, the presence of these plasmids in the studied isolates is of major concern and may mediate the horizontal transmission of antimicrobial resistance along the food chain.…”
Section: Discussionsupporting
confidence: 93%
“…The isolates belonging to ST11, ST142, and ST469 carried the gene entA associated with ROX degradation, while only ST548 samples included the determinants encoding toxins ( cdtB, pltAB ). According to the hybrid assembly, the genes encoding yersiniabactin operon ( fyuA , irp12 , ybtAEPQSTUX ) were of plasmid localization; the same picture was previously observed in S. Infantis isolates [ 19 ].…”
Section: Resultssupporting
confidence: 59%
“…ST32 was the primary ST since it is prevalent in Russia [ 19 ], together with Europe and Japan [ 7 , 17 , 41 , 42 ]. Two isolates studied belonged to ST548, and other sequence types (ST11, ST469, and ST142) had single samples, while in China the predominant ST was ST11 (12.4%) and ST469 had 3.2% [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Полногеномное секвенирование и анализ 45 российских изолятов S. Infantis с множествен ной лекарственной устойчивостью (МЛУ) из образцов куриной и мясной продукции в течение 2018-2020 гг. показало наличие bla CTXM14 у 8,9% штаммов, bla TEM1B -у 24,4% и bla TEM141 -у 2,2% штаммов [27].…”
Section: Introductionunclassified